Peran Badan Permusyawaratan Desa di dalam Pembuatan Peraturan Desa di Desa Bangun Kabupaten Dairi - Situmorang, Paulus Riswanto; Adam, Adam; Lubis, Yurial Arief (Universitas Indo Global Mandiri, 2024)
This paper aims to find out the role of the BPD in the process of making village regulations and what factors hinder it. The problem is focused on the Village Consultative Body, which is one of the most important institutions in village administration, especially in making village regulations. In order to approach this problem, theoretical references are used from seeing and directly assessing conditions and situations in the field naturally and in accordance with what is happening in the food. The data wer e collected through village consultative bodies, village heads, village secretaries and other village officials, deputy chairmen of LKMD, youth organizations and the local community and were analyzed qualitatively. This study concludes that in the implementation of the BPD's role during the design process until the completion of village regulations, it can be seen from three indicators, namely the active role, participatory and passive roles have not been fully implemented and the results of village regulations that have been ratified have not fully fulfilled the expectations of the community. this is based on several factors that become obstacles, namely, communication between BPD management and members is not well established, special budgets during the perdes design process do not exist, and commitment within the BPD institution in carrying out duties is still lacking, the resources of members of the village consultative body are still lacking. low and for experience is still lacking.